2016
DOI: 10.1038/ncomms11501
|View full text |Cite
|
Sign up to set email alerts
|

14-3-3 proteins regulate Tctp–Rheb interaction for organ growth in Drosophila

Abstract: 14-3-3 family proteins regulate multiple signalling pathways. Understanding biological functions of 14-3-3 proteins has been limited by the functional redundancy of conserved isotypes. Here we provide evidence that 14-3-3 proteins regulate two interacting components of Tor signalling in Drosophila, translationally controlled tumour protein (Tctp) and Rheb GTPase. Single knockdown of 14-3-3ɛ or 14-3-3ζ isoform does not show obvious defects in organ development but causes synergistic genetic interaction with Tct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 52 publications
(83 reference statements)
3
42
0
Order By: Relevance
“…Consistent with this, reducing Drosophila TCTP levels reduced cell size, cell number and organ size, similar to Rheb mutant phenotypes. Subsequently, this group also reported that the 14-3-3 proteins regulate the interaction between TCTP and Rheb, thus playing an important role in regulating organ growth in Drosophila (Le et al 2016). The TCTP-Rheb interaction was further confirmed for the human proteins by molecular modelling studies (Dong et al 2009).…”
Section: Tctp and Cell Growth Regulationmentioning
confidence: 88%
See 1 more Smart Citation
“…Consistent with this, reducing Drosophila TCTP levels reduced cell size, cell number and organ size, similar to Rheb mutant phenotypes. Subsequently, this group also reported that the 14-3-3 proteins regulate the interaction between TCTP and Rheb, thus playing an important role in regulating organ growth in Drosophila (Le et al 2016). The TCTP-Rheb interaction was further confirmed for the human proteins by molecular modelling studies (Dong et al 2009).…”
Section: Tctp and Cell Growth Regulationmentioning
confidence: 88%
“…Interaction partners of TCTP in this context are the small GTPase Rheb, an upstream regulator of mTOR (mechanistic target of rapamycin), and 14-3-3 proteins (Le et al 2016). Knockout of TCTP in plants (Arabidopsis thaliana) resulted in a male gametophytic phenotype with impaired pollen tube growth.…”
Section: Roles For Tctp In Early Developmentmentioning
confidence: 99%
“…Fortilin TCTP also contributes to the pathogenesis of diabetic nephropathy [150] and is important for the adaptive expansion of pancreatic β-cells in response to obesity and increased insulin requirement [36] and the regeneration of liver after hepatectomy [31]. Fortilin TCTP does this most likely by positively regulating the mTOR signaling pathway [34, 35, 5759]. The protection by fortilin TCTP of the liver against acute alcohol injury is mediated by its ability to interact with and potentiate the activity of PRX1[12].…”
Section: Discussionmentioning
confidence: 99%
“…These data suggested that fortilin TCTP promotes cell growth and proliferation during development by binding to Rheb and positively regulating its activity [34]. The same group also reported that Drosophila 14-3-3 proteins are required to promote the interaction between fortilin TCTP and Rheb, and the loss of 14-3-3-proteins critically impaired organ growth during Drosophila development [35]. It is likely that the developmental role of fortilin TCTP is both the prevention of inappropriate apoptosis and the facilitation of cell proliferation and growth through the negative and positive regulations of the apoptosis [2, 20, 21] and mTOR growth pathways [34, 35], respectively (Fig.…”
Section: Fortilintctp In Human Diseases and Developmental Abnormalmentioning
confidence: 99%
See 1 more Smart Citation